Critical Synthesis Package: Ten-Item Personality Inventory (TIPI)-A Quick Scan of Personality Structure - Anthony O. Ahmed; Barbara Jenkins (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Ten-Item Personality Inventory (TIPI), and (2) a copy of the TIPI instrument and scoring key developed by Samuel Gosling, PhD. The TIPI is a ten-item measure of personality traits and characteristics as conceptualized by the five-factor model (FFM). It assesses the big-five traits-Emotional Stability, Extraversion, Openness, Agreeableness, and Conscientiousness-using two items for each scale. In several psychometric evaluations, data collected with the TIPI has demonstrated good test-retest reliability with retest intervals as long as six weeks. In contrast, the internal consistency of the individual subscales has generally been low due to the few items in each scale. The TIPI has demonstrated good convergent and discriminant validity with other measures of personality and related constructs despite its relatively low internal consistency reliability. An advantage of the measure is its strong validity (comparable to longer personality measures) and its relative brevity that allows it to be usable in large scale studies. A limitation of the measure is that it is not adaptable to capturing the finer, narrow-bandwidth personality traits subsumed by the FFM. Another limitation is that it has only been applied in a few studies of health science education samples.